PARA-PARA ADAT SEBAGAI LEMBAGA PERADILAN ADAT PADA MASYARAKAT HUKUM ADAT PORT NUMBAY DI KOTA JAYAPURA - MAGDALENA AWI, SARA IDA (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
customarysettlementresolvedthroughthepara- para adat as judicial institution indigenouspeoples as Port Numbay hereacts as afacilitatorandmediatorin resolvingcriminalmattersand civilindigenouspeoples.Finesand penaltiesastraditionalinstruments andsettlementalternatives inindigenouscommunitiesand tribal peoples Port Numbay in Jayapura , where settlementthroughcustomarylightersanctionthanupon completionvia thenational lawso thatindigenous peoplepreferNafriresolve the issuethroughtraditional institutionsthanthroughnational law. While theobstacles encountered in thejudicialsettlementthroughcustomary Port Numbay issometimesa delaythe trialbecause ofthe absence ofone of the partiesto the disputethat isthe perpetrator , due to illness, theactordid notwantother people tointervene inproblem solving, as well as evidence ofthe witnesses andthe constraintsofvictims so thatcan complicatesettlementthroughcustomarycourt. It is suggested thatindigenousinstitutions Port Numbay to be moreactively involved inefforts toresolve thecriminalcasecustomcase,given theindigenous peoplein the city ofJayapura Port Numbay more familiarway of resolving theproblem throughcustoms . Andto indigenous Port Numbay in Jayapurato alwayssupport the existence ofthe courtoragencyof indigenouspeoplesNafriin solvingthe problems oftraditionalcriminaland civilcustomsin order to achievethe securityandwelfare ofindigenous peoplesin Port Numbay .
Keywords: Judicial Custom; Para-Para Adat; Custom Case; Indigenous Peoples Port Numbay